Efektivitas Kebijakan Moneter Non Konvensional pada BPD Indonesia di Masa Pandemi - Danang Indrajaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This article analyzes the effectiveness of non-conventional monetary policy in Indonesia. The data used is quarterly panel data covering 16 Regional Development Banks (BPD) for 9 quarters from 2019 to 2020. This study analyzes the effectiveness of quantitative easing policies on bank lending channels from monetary policy transmission. This study uses static and dynamic panel data analysis methods, namely the Individual Fixed Effects method, and the Generalized Method of Moments Analysis. The results of this study indicate that the liquidity ratio has a positive but not significant effect on credit growth. Likewise, the effect of the securities ratio is negative but not significant on credit growth. This shows that non-conventional monetary policy in Indonesia is not effective, because banks are still hesitant to channel new loans for fear of increasing non-performing loans